Wpływ wizerunku kraju pochodzenia na postrzeganie firm i produktów - wyniki badań europejskich - Daszkiewicz, Magdalena; Waniowski, Paweł (The Influence of Country of Origin Image on Perception of Firms and Products - Results of European Studies, 2006)
The article discusses how the country of origin influences firms' and their products' images. The authors describe factors influencing perception of the country of origin, emphasizing the importance of consumer ethnocentrism. The article presents examples of some European research on perceptions of the countries of origin and their meaning for firms and products evaluations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 257-266